Respuesta :

Answer:

Simplifying

10x + -5(3x + -1) = 15

Reorder the terms:

10x + -5(-1 + 3x) = 15

10x + (-1 * -5 + 3x * -5) = 15

10x + (5 + -15x) = 15

Reorder the terms:

5 + 10x + -15x = 15

Combine like terms: 10x + -15x = -5x

5 + -5x = 15

Solving

5 + -5x = 15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.

5 + -5 + -5x = 15 + -5

Combine like terms: 5 + -5 = 0

0 + -5x = 15 + -5

-5x = 15 + -5

Combine like terms: 15 + -5 = 10

-5x = 10

Divide each side by '-5'.

x = -2

Simplifying

x = -2

Step-by-step explanation: